Digitalisasi Himpunan Putusan Tarjih Muhammadiyah Berbasis Android Menggunakan Kodular - Fasbir, Muhamad; Ramli, Ramli; Wahyudin, Wahyudin (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2025)
This study aims to digitize the Himpunan Putusan Tarjih Muhammadiyah through an Android-based application developed using the Kodular platform. The goal is to improve accessibility, efficiency, and effectiveness in the dissemination of religious information. The research was motivated by challenges experienced by Muhammadiyah members in Bima Regency in accessing the printed version of the document, including limited availability, inefficient information search, and lack of real-time updates. Using the Research and Development (R&D) method with a 4D model (Define, Design, Develop, Disseminate), the application was successfully developed to convert the Himpunan Putusan Tarjih into digital formats—text and video. Validation by content and media experts resulted in excellent feasibility ratings, with an average score of 5. User testing involving 15 respondents yielded an average score of 4.78 (95.7%), indicating strong acceptance. This digital initiative marks a strategic step toward supporting credible Islamic da'wah and information dissemination in the digital ageKata kunci: Android, Digitalisasi, Himpunan putusan tarjih, Kodular